BUKTI HUBUNGAN KERAJAAN ACEH DAN KESULTANAN TURKI UTSMANI DALAM NASKAH KHOTBAH JIHAD - Moch. Syarif Hidayatullah (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2014)
AbstractRiddell’s Research (2001) shows the various elements in Islam, such asdoctrine, debate, theology, writing Manuscripts, commentary, legal, mystical, thought, and the reform movement, participate in developing the archipelago, from the 16th century until the 20th century. Islam also influences not only on the teachings and religious thought but also on writing systems and languages. In other words, the public acceptance of the Archipelago to Islam, Islam brings into acculturation with the local culture. This paper will look how the sermon to be a discourse which also influences the way of people of Aceh in the issue of jihad, it also wages a fight against the Dutch ambition to conquer Aceh as the most important regions in the archipelago at that time. The result of this research shows how the text can inflame resistance to colonization (read: Dutch) andfostering self-sacrifice anything for the sake of religion and motherland.Keywords: Sermon, Aceh war, Ottoman Turkish.